2022
DOI: 10.7554/elife.66975
|View full text |Cite
|
Sign up to set email alerts
|

Doublecortin engages the microtubule lattice through a cooperative binding mode involving its C-terminal domain

Abstract: Doublecortin (DCX) is a microtubule (MT) associated protein that regulates MT structure and function during neuronal development and mutations in DCX lead to a spectrum of neurological disorders. The structural properties of MT-bound DCX that explain these disorders are incompletely determined. Here, we describe the molecular architecture of the DCX-MT complex through an integrative modeling approach that combines data from X-ray crystallography, cryo-EM and a high-fidelity chemical crosslinking method. We dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…In addition, our MT-binding assay demonstrates that, while C-DCX itself does not bind MTs, C-DCX increases the interactions of DCX with MTs ( Figure 3B ). This suggests that the interactions between DCX and MTs are enhanced by DCX’s C-terminal domain, which is consistent with recent findings that the tail of DCX (amino acid 303 to the C-terminal end) helps to maintain the associations between DCX molecules on the MT lattice ( Rafiei et al, 2022 ).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, our MT-binding assay demonstrates that, while C-DCX itself does not bind MTs, C-DCX increases the interactions of DCX with MTs ( Figure 3B ). This suggests that the interactions between DCX and MTs are enhanced by DCX’s C-terminal domain, which is consistent with recent findings that the tail of DCX (amino acid 303 to the C-terminal end) helps to maintain the associations between DCX molecules on the MT lattice ( Rafiei et al, 2022 ).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, the overall conformation of DCX changes when DCX associates with MTs. Studies also showed that DCX dynamically associates with MTs mainly through its N-terminal R1 MT-binding domain ( Moslehi et al, 2017 ; Rafiei et al, 2022 ). However, DCX’s C-terminal region still plays a critical role in the association of DCX with MTs despite C-DCX’s inability to directly bind to MTs ( Rafiei et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations